Analisis Tindak Tutur Ilokusi dalam Video Pembelajaran Kelas 12 SMA/SMK dalam Kanal YouTube Suparti Timbul - Moh. Ilman Akbar Al Izaaki; Hanifah Ainurohmah; Ainna Galuh Pratiwi; Anggita Rahma Aprilianti; Deane Rahmah Indriawati; Asep Purwo Yudi Utomo; Iwan Hardi Saputro; Ramadhan Kusuma Yuda (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This study aims to analyze the illocutionary speech acts used by the teacher in the Indonesian language learning videos on the YouTube channel "Suparti Timbul." Illocutionary speech acts consist of several types, including assertive, directive, declarative, commissive, and expressive, each playing an important role in the learning process. This study employs a descriptive qualitative approach to identify and interpret the various speech acts found in the learning videos. The results show that the teacher uses assertive speech acts to convey information, directive speech acts to give instructions and motivate students, declarative speech acts to create a conducive learning atmosphere, commissive speech acts to make commitments regarding the learning material, and expressive speech acts to express positive expectations. These speech acts are crucial for fostering interactive communication and enhancing the efficacy of online education. Based on the study's findings, educators and others who create educational content are advised to focus more on the proper use of speech acts to make sure the message is clear and useful for enhancing student comprehension.